ANALYSIS OF THE PERFORMANCE DETERMINANTS OF NON-ASN TEACHERS FROM THE PERSPECTIVE OF WORK MOTIVATION AND LEADERSHIP STYLE OF STATE ELEMENTARY SCHOOLS IN KLATEN UTARA DISTRICT, KLATEN REGENCY - Maryani, Dwi (Universitas Negeri Yogyakarta, 2023)
Abstractâˆ’ Study This aim for know influence in a manner simultaneous nor Partial between motivation work and style leadership head school to the performance of PNS teachers in Public Elementary Schools throughout the District North Klaten, Regency Klaten. Method study This use design study quantitative. The population in this study were all Non-ASN Coordinating Teachers for the North Klaten District of the Klaten Regency Education Office. The sampling technique uses Total Quota Sampling with 74 samples. Data collection techniques using observation, documentation and surveys using questionnaires. The instrument test uses validity and reliability tests. Data analysis technique using test multiple linear regression hypothesis, t test, F test and R2 test. The results of the study showed that (1) there was an influence of teacher work motivation on the performance of non- ASN teachers in public elementary schools in North Klaten District, Klaten Regency with the results of t count of 3.809 and a sig value of 0.000, (2) There is an influence of the principal's leadership on the performance of Non- ASN teachers in Public Elementary Schools in North Klaten District, Klaten Regency with the result t count of 2.784 and a sig value of 0.007 and (3) Simultaneously there is an influence of teacher work motivation and principal leadership on the performance of Non- ASN teachers in Public Elementary Schools in North Klaten District, Klaten Regency with an F count of 16.285 and a significance of 0.000. Keywords: work motivation, principal leadership style, teacher performance.